Pengaruh Deklinasi Matahari terhadap parameter cuaca wilayah malang dan sekitarnya - Achmad Sasmito; Alfan Sukmana Praja; Linda Fitrotul Muzayanah; Rahayu Sapta sri Sudewi (Department of Physics, Sebelas Maret University, 2021)
Cold temperatures occur in the Dieng and Lumajang highlands from the end of July to August 2020. At almost the same time, hot temperatures also occur in the United States, Japan, and Spain. This study discusses the effect of declination of the sun on weather parameters in Malang and its surroundings. Besides, it also discusses a physical and dynamic review of the occurrence of hot air temperatures in the northern hemisphere (BBU) with cold temperatures in the southern hemisphere (BBS). The data used are numerical data of solar radiation of the atmosphere and observation data from AWS which includes elements of global radiation, temperature, and surface air humidity. Data samples were taken from Malang Climatology Station and Karang Kates Geophysical Station which represent BBS and weather information from BBU. Estimation of cold temperatures in Ranu Pani, Lumajang was carried out using the lapse rate model. Cold temperatures that occur in the East Java region are influenced by the declination of the Sun, solar radiation, the transmissivity coefficient, and the temperature advection process from Australia. When the sun is in the north, there are cold temperatures in the southern part of the earth and vice versa. The occurrence of hot or cold temperatures in each region is also influenced by the composition of gases in the atmosphere, geography, topography, and the influence of advection due to the influence of the surrounding air.